Optimizing the amount of concentration and temperature of substances undergoing chemical reaction using response surface methodology - Shadi Bolouki Far; Seyyed Amirreza Abdollahi; As'ad Alizadeh; Arsam Bostani; Hussein Zekri; Pooya Pasha; Hossein Nabi (International Journal of Thermofluids, 2023)
In this article, we investigate the temperature and concentration of particles around a vessel in three different locations using the reaction and diffusion relations, the reaction between three chemical particles, and the relationship between temperature changes and the rate of chemical reaction. The goal and necessity of this research is that we were able to visualize these chemical agents by using a finite mathematical fluid method, changing the physical properties of the materials, and learning about how chemical reactions affect concentration and temperature and how they relate to one another. The innovation of this essay is that it compares the parameters of concentration and temperature of substances involved in chemical reactions in different places of the inner vessel to the larger vessel, with and without the presence of a heat source. We also achieved the highest and best efficiency of concentration and heat transfer of chemical reactions (a), (b), and (c) using the finite method in Flexpde, Ansys fluent, and Design - Expert software (c). The obtained results show that the concentration changes significantly as the temperature of the reactants rises and more heat is released. According to the test conducted with the RSM method, the best efficiency and optimization of temperature and concentration parameters occurs in heat source = 2.555°, diffusivity = 0.025 and diameter of inner vessel = 3.144 cm.